Analyst coverage and stock return synchronicity: evidence from regulation changes in China's IPO market. Issue 47 (7th October 2016) - Bai, Xuelian; Wang, Fangjun; Zhang, Junrui
ABSTRACT: This article investigates the relation between analyst coverage and stock return synchronicity in the IPO market. Using a unique data set in China from 2005 to 2012, we find a significantly different effect of analyst coverage on synchronicity before and after the implementation of important 2009 IPO regulation changes in China. Specifically, we document that analyst coverage reduces synchronicity but that this effect is significant only after 2009. In addition, we extend this research to further distinguish the information production role of underwriter and independent analysts. We find that prior to 2009, underwriter analysts' coverage decreases synchronicity but independent analysts' coverage does not. However, in the post-2009 period, both types of analyst coverage are significantly and inversely associated with synchronicity. Overall, our results support analysts' role as producers of firm-specific information in an emerging IPO market and shows that this role depends on the institutional environment.